The Poleng Motifs in Balinese Women’s Clothing / Bali Kadın Giyiminde Poleng Motifleri - Arya Pageh Wibawa*; Imam Santosa**; Setiawan Sabana***; Achmad Haldani Destiarmand**** (Folklor/Edebiyat, 2023)
This article aims to find the meaning of the representation of the poleng motif in Balinese women’s clothing. The issues are as follows: 1) How is the poleng motif represented on Balinese women’s clothing? and 2) Does the poleng motif in Balinese women’s clothing have a symbolic communication meaning?. In traditional Balinese culture, the poleng motif in Balinese women’s clothing has a bad meaning. Most Balinese women note that Poleng patterned clothing is used in a cultural context, not because it has a bad meaning. Qualitative methods were heavily relied upon in writing this article, starting with collecting primary data from informants such as pecalang and community leaders. Secondary data sources were obtained from ancient Balinese literature and research journals through library research. Data analysis uses symbol theory and reception theory, which are operationalized qualitatively and interpreted. Results from the study show that: 1) The way the poleng motif on Balinese women’s clothing representation is sacred, sets forth a task identity, and is the identity of Balinese fashion identity; and 2) The poleng motif on Balinese women’s clothing always has a symbolic communicative meaning in traditional ceremonial activities. Balinese women who use the poleng motif prioritizes the representation of fashion identity rather than profession or kawisesan in symbolic communication in a cultural context.